Activation of Src Mediates PDGF-Induced Smad1 Phosphorylation and Contributes to the Progression of Glomerulosclerosis in Glomerulonephritis - Mima, Akira (Public Library of Science, 2011)
Platelet-derived growth factor (PDGF) plays critical roles in mesangial cell (MC) proliferation in mesangial proliferative glomerulonephritis. We showed previously that Smad1 contributes to PDGF-dependent proliferation of MCs, but the mechanism by which Smad1 is activated by PDGF is not precisely known. Here we examined the role of c-Src tyrosine kinase in the proliferative change of MCs. Experimental mesangial proliferative glomerulonephritis (Thy1 GN) was induced by a single intravenous injection of anti-rat Thy-1.1 monoclonal antibody. In Thy1 GN, MC proliferation and type IV collagen (Col4) expression peaked on day 6. Immunohistochemical staining for the expression of phospho-Src (pSrc), phospho-Smad1 (pSmad1), Col4, and smooth muscle α-actin (SMA) revealed that the activation of c-Src and Smad1 signals in glomeruli peaked on day 6, consistent with the peak of mesangial proliferation. When treated with PP2, a Src inhibitor, both mesangial proliferation and sclerosis were significantly reduced. PP2 administration also significantly reduced pSmad1, Col4, and SMA expression. PDGF induced Col4 synthesis in association with increased expression of pSrc and pSmad1 in cultured MCs. In addition, PP2 reduced Col4 synthesis along with decreased pSrc and pSmad1 protein expression in vitro. Moreover, the addition of siRNA against c-Src significantly reduced the phosphorylation of Smad1 and the overproduction of Col4. These results provide new evidence that the activation of Src/Smad1 signaling pathway plays a key role in the development of glomerulosclerosis in experimental glomerulonephritis.